Facilitating the 'Least Restrictive Option and Maximising Independence' under Section 115 Mental Health Act 1983. Issue 4 (4th July 2020) - Rooke, Rachael
Abstract : One of the main responsibilities of the Approved Mental Health Professional (AMHP) is coordinating Mental Health Act (MHA) Assessments. This can include making applications for compulsory admission, and applying the guiding principles of the MHA including, the 'Least restrictive option and maximising independence' when considering alternatives to compulsory admission. A MHA assessment is usually requested during mental health crisis when alternatives to admission are exhausted. Literature refers to the controlling and coercive elements of the AMHP role, lack of community resources, and the increasing number of compulsory admissions direct from the community. There is less research on the wider role of the AMHP and its potential to avert crisis. Included in the main AMHP functions is the authority under section 115 MHA to enter and inspect, with 'reasonable cause', premises in relation to 'mentally disordered patients'. This authority may enable AMHPs to intervene without coordinating a MHA assessment whilst meeting the legal obligation to 'consider the patient's case' under Section 13 (1) MHA. The role of the AMHP as a 'legal protector' of human rights and their expertise in averting crisis is discussed. This article concludes with recommendations for AMHP practice.